ASPEK RELIGIUSITAS NOVEL MANTRA PEJINAK ULAR KARYA Kuntowijoyo: KAJIAN SEMIOTIK DAN IMPLEMENTASINYA SEBAGAI BAHAN AJAR SASTRA DI SMP - Parini, Sri (Jurnal Penelitian Humaniora, 2014)
This study examines three issues, namely: (1) the structure of the Mantra Pejinak Ular (MPU), (2) the meaning of religiosity of the novel based on semiotic perspective, and (3) the pedagogical implication of finding as literary materials in Junior High School. This research uses descriptive qualitative method. The result of analysis indicates as follows: (1) there is a close relationship between the building elements of the novel; (2) the religiosity aspects in this novel includes the understanding of the main truth of oneself, thankful to Allah, the religious practice (worship) followed by good deeds, changing oneself, asking others to concern truth, defending the truth, awareness for the charity, art work recalling God, the belief of the Javanese society, and the existence of salvation events.